Land Conservation Initiatives Around MT. Elgon National Park, Eastern Uganda - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The goal of this paper is to provide an investigation of the land conservation strategies adopted by farmers to control land degradation around Mt. Elgon National Park, Uganda. Primary data were obtained through household survey conducted in Mutushet and Kortek parishes, Kapc.horwa district between June to December, 2003. The differences between adopters and non-adopters of land conservation practices in terms of contact with extension workers, tribe, size of productive family labour, membership to farmer organization, education level, and participation in communal land management activities and frequency of natural hazards on private agricultural landfj were examined Farmers have increasingly adopted different structural measures like terraced farming, construction of waterways, check dams, retention walls, and gull control. Similarly, they have also adopted different biological measures including alley cropping, bamboo plantation in gullies, mulching and applied organic and inorganic fertilizers to control land degradation. However, farmers have not been able to control land degradation to a great extent due to relatively weak technological backup by concerned agencies. It was concluded that severity of land degradation is higher in the parishes with traditional farming methods because farmers are not provided with the necessary technical advisory services.